Influence of TiO2 incorporation methods on NOx abatement in Engineered Cementitious Composites. (10th October 2019) - Xu, Mingfeng; Bao, Yi; Wu, Kai; Xia, Tian; Clack, Herek L.; Shi, Huisheng; Li, Victor C.
Highlights: Effect of three TiO2 incorporation methods on photocatalytic (PC) efficiency of ECC is studied. Effect of three TiO2 incorporation methods on mechanical properties of ECC is studied. Porous microstructure promotes the PC efficiency by increasing the exposure surface of ECC. Alkaline environment of ECC consumes nitrate acid and promotes PC reactions. Abstract: Titanium dioxide (TiO2 ) nanoparticles have been incorporated in concrete to impart photocatalytic (PC) properties, such as the self-cleaning and air purification functionalities, which are dependent on PC reactions near the exterior surfaces of the concrete exposed to light. This study experimentally investigates the effect of three TiO2 incorporation methods and surface patterns on the air-purifying functionality and mechanical properties of PC Engineered Cementitious Composites (PC-ECC). The air-purifying functionality was evaluated by measuring the nitrogen oxides (NOx ) concentration change with the presence of PC-ECC plate specimens exposed to ultraviolet (UV) irradiation; uniaxial tensile and four-point bending tests were conducted to evaluate the tensile and flexural properties of the PC-ECC plates; scanning electron microscopy (SEM) was used to characterize the surface morphology of the plates; energy dispersive spectroscopy (EDS) was used to map the element distribution on the surface. Test results indicate that the amount of TiO2 nanoparticles is reduced by 90% when TiO2 is incorporated through a thin layer on the exterior surface of the ECC plate, while PC functionality and mechanical properties are retained. Incorporating TiO2 through polyurethane coating reduces the NOx abatement efficiency by 70–80%, compared with directly mixing the TiO2 nanoparticles in ECC. The reduced PC efficiency is attributed to the dense microstructure and low alkali content of the coating. This study advances the fundamental knowledge for designing functionally graded PC concrete with optimized PC efficiency and mechanical properties.